TEACHER STRATEGIES USING STORY-TELLING METHOD: INCREASE THE COURAGE OF STUDENS TO SPEAK - Septiani, Rizka Ayu; Sulastri, Lili (IKIP Siliwangi, 2019)
This study is a Classroom Research Action. It is intended to increase the courage of students to perform speaking of at the eighth grade students of SMP Negeri 2 Cilamaya Kulon by using storytelling. Storytelling is telling something about an act or an event and is delivered orally in to share experiences and knowledge with other persons. Storytelling may stimulate the interest of children in reading a book. it helps the learners of EFL become more self-confident to express themselves spontaneously and creatively. The instruments of the investigation are observation sheet, field notes, and speaking test. The result of the research showed that there was improvement from Cycle I to Cycle II in the participation of students in introduction, discussion and practice. In the students’ achievement Cycle I, 9 students got 70, 5 students get 77 and 2 students got score 82 while in Cycle II, 16 student got 70, 7 students got 77 and 7 students got 82. Storytelling have a significant impact on improving courage of students to speak.